(untitled) (The Research of Medical Science Review, 2025)
Background: Frequent headaches and related disability define the crippling disorder known as chronic migraines, which seriously affects patients' health. Emerging as a potential preventive treatment for chronic migraines is botulinum toxin. Objectives: This study assessed the effectiveness, safety and patient-reported outcomes of botulinum toxin in lowering headache frequency, severity and disability in chronic migraine sufferings. Methods: At a tertiary care center in Rawalpindi, this prospective observational study spanning July 2024 through December 2024 was undertaken. Convenient sampling enrolled 180 individuals total diagnosed with persistent migraines. Participants were followed up at 4, 12 and 24 weeks after receiving botulinum toxin per the PREEMPT regimen. Measuring headache frequency and intensity with Numeric Rating Scale (NRS) and Migraine Disability Assessment (MIDAS) scores, patient satisfaction, adherence, quality of life was determined by WHOQOL-BREF. Results: Headache days per month dropped from 21.4 ± 3.8 at baseline to 7.4 ± 2.2 at 24 weeks (p < 0.001). From 7.9 ± 1.2 and 52.6 ± 14.8 at baseline to 2.7 ± 1.0 and 15.3 ± 6.7, respectively, NRS and MIDAS scores shown similar declines (p < 0.001). Across all spheres, quality-of- life ratings greatly improved; physical health rose from 52.3 ± 9.4 to 78.5 ± 7.2 (p < 0.001). Adherence rates were high—88.9% at 24 weeks—and adverse effects were few—2.8% at 24 weeks. Conclusion: Ultimately, botulinum toxin improved quality of life by significantly lowering headache frequency, severity and disability while also being useful and well-tolerable treatment for chronic migraine. Its low negative effects and great adherence helped to justify its long-term preventive role.